Comercio internacional y crecimiento económico del Perú, empleo y riqueza desde 2008 hasta 2021 - Aspillaga Barrantes, Angélica (2023)
Perú has historically been an exporter country that in recent years has experienced an increase in its total exports, especially in the non-traditional ones. The problem arises of defining whether opening to international trade and eliminating tariff barriers are beneficial for the Peruvian economy. This research analyzes the development of International Trade between 2008 and 2021 as well as the development of Economic Growth, through the measurement of GDP, to evaluate the impact of trade on said growth and find if there is a correlation between the two and if it was positive. It also analyzes whether, if there is such a correlation, if it generates an increase through the generation of value with non-traditional exports and thus an increase in wealth through employment. Various research works have been analyzed in the empirical literature, as well as the variables and the econometric models used in them, if any, and their conclusions. In this way, it is possible to find different results given the different policies of open trade and the individual realities of each country. An MCO model is used that has as an endogenous variable the real GDP and as variables to the Traditional and Non-Traditional Exports, Imports, Real Exchange Rate Index. The results of the econometric model are contrasted with the results of similar works and coincident results are found many times, which reaffirms the positive effect, as well as the correct use of the chosen econometric model (MCO).